Valence of agents and recipients moderates the side-effect effect: two within-subjects, multi-item conceptual replications - Stewart, Suzanne L. K.; Kennedy, Bradley J.; Haigh, Matthew (Journal of cognitive psychology (Hove, England), 2022)
The side-effect effect (SEE) demonstrates that the valence of an unintended side effect influences intentionality judgements; people assess harmful (helpful) side effects as (un)intentional. Some evidence suggests that the SEE can be moderated by factors relating to the side effect's causal agent and to its recipient. However, these findings are often derived from between-subjects studies with a single or few items, limiting generalisability. Our two within-subjects experiments utilised multiple items and successfully conceptually replicated these patterns of findings. Cumulative link mixed models showed the valence of both the agent and the recipient moderated intentionality and accountability ratings. This supports the view that people represent and consider multiple factors of a SEE scenario when judging intentionality. Importantly, it also demonstrates the applicability of multi-vignette, within-subjects approaches for generalising the effect to the wider population, within individuals, and to a multitude of potential scenarios. For open materials, data, and code, see https://www.doi.org/10.17605/OSF.IO/5MGKN .